Decrease in plasma B-type natriuretic peptide early after initiation of cardiac resynchronization therapy predicts clinical improvement at 12 months - Kubánek, Milos; Málek, Ivan; Bytesník, Jan; Frídl, Petr; Riedlbauchová, Lucie; Karasová, Ludmila; Lánská, Vĕra; Kautzner, Josef (European journal of heart failure, 2006)
BACKGROUND: Decrease in neurohormonal activation during pharmacotherapy for chronic heart failure (CHF) is associated with haemodynamic and clinical improvement. We tested the hypothesis that changes in neurohormonal activation after initiation of cardiac resynchronization therapy (CRT) predict its long-term clinical effect. METHODS: The study group included 43 patients with CHF (37 males, mean age 62+/-9 years, NYHA class 3.2+/-0.4, QRS duration 195+/-24 ms) who underwent successful implantation of a CRT system. Pharmacotherapy remained stable during the first 3 months of follow-up. Plasma levels of B-type natriuretic peptide (BNP) and big endothelin-1 (big ET-1) were evaluated before and 3 months after implantation. Clinical, echocardiographic and exercise parameters were monitored for a mean period of 25.8+/-6.7 months. RESULTS: At 12 months of follow-up 13 non-responders were identified (no improvement in NYHA class (n=10), urgent heart transplantation (n=2) and death due to progressive heart failure (n=1)). CRT resulted in a significant reduction in neurohormone levels (BNP 345.4+/-346 vs. 267.7+/-320.8 pg/ml, p<0.01, big ET-1 3.11+/-1.50 vs. 2.50+/-1.56 fmol/ml p<0.05), especially in responders. Percentage change in BNP level was a stronger predictor of long-term clinical improvement than clinical, echocardiographic and exercise parameters at 3 months of follow-up. CONCLUSIONS: Percentage change in plasma BNP levels from baseline to 3 months was the strongest predictor of long-term response to CRT and may have potential to predict outcome.
Keywords: senioři; Disease Progression; senioři nad 80 let; progrese nemoci; Prognosis; Time Factors; Cardiac Pacing, Artificial; výsledek terapie; Middle Aged; mužské pohlaví; Adult; kardiostimulace umělá; Follow-Up Studies; následné studie; Aged, 80 and over; prognóza; Humans; biologické markery; ledviny; časové faktory; lidé středního věku; srdeční selhání; Natriuretic Peptide, Brain; dospělí; natriuretický peptid typu B; Biomarkers; Kidney; Aged; Treatment Outcome; Heart Failure; lidé; Male